Implementation of Effective Cough Training to Improve Airway Clearance in Asthma Patients: A Nursing Care Process Case Study in the Emergency Department - Oktavianingsih, Linda; Kurniawan, Rudi; Gunawan, Asep; Novianti, Elis (Jurnal Vocational Nursing Sciences (VNUS), 2025)
Asthma is a chronic respiratory disorder that remains a major public health concern, particularly in areas with high pollution levels. One of the most frequent nursing problems among asthma patients is ineffective airway clearance caused by mucus retention. Effective cough training is a non-pharmacological nursing intervention aimed at facilitating secretion removal and improving respiratory function. This case study evaluated the effectiveness of cough training in improving airway clearance in an asthma patient treated in the emergency department. A descriptive case study design using the nursing care process assessment, diagnosis, intervention, implementation, and evaluation was applied. Data were collected through interviews, physical examinations, observations, and documentation for two days. The intervention consisted of deep nasal inhalation for four seconds, breath-holding for two seconds, exhalation through pursed lips for eight seconds, followed by a controlled cough. After two days, improvements were observed in respiratory rate (from 26 to 22 breaths per minute), oxygen saturation (from 90% to 95%), and mucus expectoration. The patient was able to perform the technique independently after education and guided practice. These findings indicate that effective cough training is a simple, evidence-based nursing intervention that enhances airway clearance and oxygenation and should be integrated into emergency asthma care to prevent complications.